The sage and the people : the confucian revival in China - Billioud, Sébastien (O. U. P, 2015)
After a century during which Confucianism was viewed by academics as a relic of the imperial past or, at best, a philosophical resource, its striking comeback in Chinese society today raises a number of questions about the role that this ancient tradition-re-appropriated, reinvented, and sometimes instrumentalized-might play in a contemporary context.